Characteristics of aerial dust in finishing buildings - A J Heber; M Stroik (Kansas Agricultural Experiment Station Research Reports, 1987)
Eleven finishing units were surveyed to study the characteristics of aerial dust and factors that influence dust concentrations. Feed dust was the major portion of the total dust mass and can be minimized with feed additives, less feed wastage, enclosed feed delivery, and periodic cleaning. Ventilation was the primary method for dust removal. Naturally ventilated buildings had higher dust concentrations than mechanically ventilated buildings because of lower average airflow rates, especially during cold weather. Swine workers can minimize respiratory symptoms by wearing face masks.; Swine Day, Manhattan, KS, November 19, 1987
Keywords: Swine day; 1987; Kansas Agricultural Experiment Station contribution; no. 88-125-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 528; Swine; Aerial dust; Finishing pigs; Ventilation